Changing Relationship Between Tibetan Plateau Temperature and South China Sea Summer Monsoon Precipitation - Liang, Mei; Xu, Jianjun; Chan, Johnny C. L.; Wu, Liguang; Xu, Xiangde (Frontiers in Environmental Science, 2020)
The present study documents the changes in the relationship between the Tibetan Plateau summer surface temperature (TPST) and the South China Sea summer monsoon precipitation (SCSSMP). A stepwise regression model is used to exclude the signals of global warming, El Niño–Southern Oscillation (ENSO), western North Pacific Subtropical High (WNPSH), Atlantic Multidecadal Oscillation (AMO) and Pacific Decadal Oscillation (PDO). The results indicate that the relationship between TPST–SCSSMP changes with time, going from a negative correlation during the period of 1980–1994 to an obvious positive correlation during 1998–2016 in the South China Sea. Meanwhile, the negative correlation between TPSST and the East Asia subtropical front (Meiyu) is enhanced during 1998–2016. This change in the TPSST–SCSSMP relationship is associated with the change of the atmospheric circulation, which is mainly due to TPSST interdecadal variation. A wave–like structure at the low latitude moves eastward along the low–level monsoon flow, and a strong cyclonic circulation is apparent in the southwestern part of the Plateau, including the Indochina Peninsula, South China Sea, and the ocean to the east of the Philippines, which is consistent with the negative correlation between TPST and Outgoing Longwave Radiation (OLR). The increase in water–vapor convergence and more favorable convection conditions lead to more precipitation in the region after the late 1990s. The present results suggest that, in a changing climate, we should be cautious when using predictor with interdecadal variations.